2019
DOI: 10.1002/jor.24554
|View full text |Cite
|
Sign up to set email alerts
|

In vitro test methods for seating and fretting corrosion behavior of modular metal‐on‐metal acetabular tapers

Abstract: Retrieval studies show that metal-on-metal acetabular shell-liner tapers are susceptible to corrosion, which is hypothesized to arise from mechanically-assisted crevice corrosion (MACC). The role of materials on MACC of acetabular tapers has not been previously studied. In vitro tests of seating, pushout, and fretting corrosion performance of acetabular tapers are presented to assess the role of material combinations (Ti-6Al-4V shells, HC CoCrMo, LC CoCrMo, and 316L SS liners). The acetabular tapers were wetas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…In engagement regions, there is some evidence of material transfer from the interfacing titanium shells, visible as light contrast regions in backscatter SEM mode, and confirmed by EDS analysis. A recent study by Shenoy et al 13 shows the actual area in contact is minimal compared to the entire shell-liner taper interface available for contact, which explains the low fretting currents (under 1 μA) recorded in the short-term in vitro fretting corrosion tests. This was corroborated in this study, where we found dispersed regions of fretting, indicating minimal direct contact within the engagement region.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In engagement regions, there is some evidence of material transfer from the interfacing titanium shells, visible as light contrast regions in backscatter SEM mode, and confirmed by EDS analysis. A recent study by Shenoy et al 13 shows the actual area in contact is minimal compared to the entire shell-liner taper interface available for contact, which explains the low fretting currents (under 1 μA) recorded in the short-term in vitro fretting corrosion tests. This was corroborated in this study, where we found dispersed regions of fretting, indicating minimal direct contact within the engagement region.…”
Section: Discussionmentioning
confidence: 98%
“…Note the antirotation tabs and the lower engagement region (marked in red) and the noncontact region between the tabs (white arrow). Figure adapted from Shenoy et al 13 backscattered image, since these generate the most backscattered electrons. Thus, we can distinguish between different surface features compositionally using SEM imaging.…”
Section: Imaging Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Tribocorrosion performance of two commercial modular acetabular designs was assessed during a long term, three million cycle intermittent test. Previous studies have not been performed for this duration (roughly 3 years of clinical use) 12 . This method provides a quantitative assessment based on fretting currents, resulting in a comparative analysis of fretting corrosion damage in the taper designs in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…This interface has been of increasing interest in recent years as a possible source of debris and ions. [42][43][44] While not part of the bearing surface degradation here is still relevant to device performance. With increased inclination the load vector will have shifted more to one side of the cup, closer to the vertical, possibly resulting in a more severe fretting interface.…”
Section: Discussionmentioning
confidence: 99%